A new small pliopithecoid primate from the Middle Miocene of Thailand. Issue 88 (November 2015) - Chaimanee, Yaowalak; Lazzari, Vincent; Benammi, Mouloud; Euriat, Adélaïde; Jaeger, Jean-Jacques
Abstract: Pliopithecoids represent a monophyletic group of putative stem catarrhines whose evolutionary history is incompletely known. They have been recorded from Europe and Asia, between the late Early Miocene and the Late Miocene. Asian pliopithecoids are less well documented than their European counterparts, often being represented by a fragmentary fossil record. New discoveries are therefore critical to reconstruct the evolutionary history of the whole group. Here, we describe two isolated molars from Ban San Klang, a late Middle Miocene locality in northern Thailand, which confirms the presence of pliopithecoids in Southeast Asia. The lower molar had originally been described as being that of a dendropithecoid, but it was later recognized as pertaining to a pliopithecoid. The discovery, in the same locality, of an additional upper molar attributed to the same species confirms the pliopithecoid status of this taxon and highlights its distinctiveness with respect to other known Asian pliopithecoids. However, the mosaic of primitive and autapomorphic features characterizing this Thai fossil, as well as its limited anatomical representation, preclude us from assigning it to either of the known pliopithecid subfamilies. Nevertheless, it represents the only pliopithecoid in Southeast Asia and displays a mosaic of unique characters which emphasizes the peculiarity of that province, as suggested previously with respect to its hominoid primate.